Process evaluation of the Healthy Primary School of the Future: the key learning points - N. H. M. Bartelink; P. van Assema; M. W. J. Jansen; H. H. C. M. Savelberg; G. F. Moore; J. Hawkins; S. P. J. Kremers (BMC, 2019)
Abstract Background While schools have potential to contribute to children's health and healthy behaviour, embedding health promotion within complex school systems is challenging. The 'Healthy Primary School of the Future' (HPSF) is an initiative that aims to integrate health and well-being into school systems. Central to HPSF are two top-down changes that are hypothesized as being positively disruptive to the Dutch school system: daily free healthy lunches and structured physical activity sessions. These changes are expected to create momentum for bottom-up processes leading to additional health-promoting changes. Using a programme theory, this paper explores the processes through which HPSF and the school context adapt to one another. The aim is to generate and share knowledge and experiences on how to implement changes in the complex school system to integrate school health promotion. Methods The current study involved a mixed methods process evaluation with a contextual action-oriented research approach. The processes of change were investigated in four Dutch primary schools during the development year (2014-2015) and the first two years of implementation (2015-2017) of HPSF. The schools (each with 15-26 teachers and 233-389 children) were in low socio-economic status areas. Measurements included interviews, questionnaires, observations, and analysis of minutes of meetings. Results Top-down advice, combined with bottom-up involvement and external practical support were key facilitators in embedding HPSF within the schools' contexts. Sufficient coordination and communication at the school level, team cohesion, and feedback loops enhanced implementation of the changes. Implementation of the healthy lunch appeared to be disruptive and create momentum for additional health-promoting changes. Conclusions Initiating highly visible positive disruptions to improve school health can act as a catalyst for wider school health promotion efforts. Conditions to create a positive disruption are enough time, and sufficient bottom-up involvement, external support, team cohesion and coordination. The focus should be on each specific school, as each school has their own starting point and process of change. Trial registration The study was retrospectively registered in the ClinicalTrials.gov database on 14 June 2016 (NCT02800616).